GSTM1 and GSTT1 null polymorphisms and male infertility risk: an updated meta-analysis encompassing 6934 subjects - Wu, Wei; Lu, Jing; Tang, Qiuqin; Zhang, Simin; Yuan, Beilei; Li, Jing; Wu, Di; Sun, Hong; Lu, Chuncheng; Xia, Yankai; Chen, Daozhen; Sha, Jiahao; et al. (Scientific reports, 2013)
Published data on the association between the GST genes polymorphisms and male infertility risk are inconclusive. We investigated GST genes polymorphisms in a large sample size case-control study and conducted a literature-based meta-analysis of 6934 individuals. Our case-control study showed the GSTM1 null genotype was significantly associated with idiopathic oligozoospermia, while the null genotype of GSTT1 was significantly associated with normozoospermia and azoospermia. Additionally, significantly elevated GSTT1 expression levels were observed in present genotype compared with null genotype. In the meta-analysis, the null genotype of GSTM1 was associated with a significantly increased risk of male infertility. Furthermore, a stratification analysis showed that the risk of GSTM1 polymorphism was associated with male infertility in both Asian and Caucasian groups. Further studies of GSTM1 and GSTT1 with their biological functions are needed to understand the role of these genes in the development of male infertility.